PERALIHAN HARTA PUSAKA TINGGI MENURUT HUKUM ADAT DAN HUKUM ISLAM (Studi Kasus di Jorong Nan IX Nagari Salimpaung) - Arizon Ridwan; Zulkifli Zulkifli; Amri Effendi (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study examines the transfer of high inheritance according to customary law and Islamic law in Jorong Nan IX Nagari Salimpaung. Using a qualitative approach, this study found that the factors that caused the transfer of high inheritance in Jorong Nan IX Nagari Salimpaung were members of the clan who wanted to build a house on high inheritance; there is one people whose descendants are almost extinct; clan members fight over high heirlooms; Members of the clan do not want to rotate the high inheritance until problems arise, even to the point of being physically involved in fighting over it. According to customary law, the transfer of high inheritance in Jorong Nan IX Nagari Salimpaung is considered wrong because it violates existing customary rules. Meanwhile, in terms of Islamic law, the transfer of high heirloom assets by dividing them into private property for members of the clan and being taken over into the private property of Tungganai which occurred in Jorong Nan IX Nagari Salimpaung is considered permissible. The actions of a Tungganai include Istihsan bi al-Maslahah, namely taking advantage and rejecting harm.